1-A-D-18. A Study on improvement of character input performance for a P300 speller. Issue 6 (June 2015) - Furuhashi, Takeshi; Yoshikawa, Tomohiro; Kawai, Kohei; Yamamoto, Yuya; Hoshiyama, Minoru
Abstract : A P300 speller, which is equipment for character input utilizing an event-related potential (ERP), was tested clinically in patients with amyotrophic lateral sclerosis (ALS). Improvement of character input speed and reduction of data acquisition time for pre-training were evaluated. The authors developed a stimulus presentation method named reliability based automatic repeat request (RB-ARQ), which dynamically discontinues stimulus presentation based on the reliability of discriminant function, an N-gram method which calculates this reliability based on the transition probabilities of Japanese letters, and an incremental learning method which uses on-line EEG data for updating the discriminant function on-line. The P300 speller incorporating the RB-ARQ and N-gram method was tested with four ALS patients on ventilator in sickrooms with plural beds in two hospitals. The utility, an index for character input speed, of the proposed method was 3.3 times higher than that of the conventional averaging method. It took approximately 10 s to input a character on average. The incremental learning method was tested in simulation using EEG data collected from two patients a half year ago and another patient a week ago for the pre-training. The proposed method achieved zero acquisition time at the start of re-use of the speller.